Coercion and Consent in Employment: From Contract to Civic Republicanism - Bonner Cochran, Augustus (Labuta: Revista Eletrônica de Direito do Trabalho e Previdência, 2024)
Although regulated by local, state, and national law, the employment relationship in the United States remains predominantly a negotiated model, with the bulk of terms and conditions of work determined by the employment contract, individual or collective. Rooted in philosophical liberalism, the essence of free labor is defined by the consent of the parties to employment. After a period of abstract ideological laissez-faire (the Lochner Era), New Deal legislation and jurisprudence brought an element of realism to labor law, seeking to remedy problems of power imbalance by encouraging collective bargaining with the National Labor Relations Act, placing a floor under working conditions with the Fair Labor Standards Act, and after WWII, countering discrimination with Title VII of the Civil Rights Act. With the “right turn” of the federal judiciary, however, accelerated by the consolidation of a conservative “supermajority” on the U.S. Supreme Court, protective regulation is being drastically undermined and worker frustrations are growing, as some commentators even warn of a return to a “new Lochner Era.” Instead of seeking simply a more realistic refurbishing of “consent,” some labor advocates are accompanying a revival of civic republicanism as a constitutional ideology in calling for a republican redefinition of freedom as non-domination at work and for empowered worker voice within firms as well as stronger democratic citizenship for workers in economic and political life.